A reappraisal of Stegastes species occurring in the South Atlantic using morphological and molecular data - de Souza, Allyson Santos; Rosa, Ricardo de Souza; Soares, Rodrigo Xavier; de Lima-Filho, Paulo Augusto; de Oliveira, Claudio [UNESP]; Shibatta, Oscar Akio; Molina, Wagner Franco (Springer Nature, 2017)
The taxonomic status of Pomacentridae species can be difficult to determine, due to the high diversity, and in some cases, poorly understood characters, such as color patterns. Although Stegastes rocasensis, endemic to the Rocas atoll and Fernando de Noronha archipelago, and S. sanctipauli, endemic to the São Pedro and São Paulo archipelago, differ in color pattern, they exhibit similar morphological characters and largely overlapping counts of fin rays and lateral-line scales. Another nominal insular species, S. trindadensis, has recently been synonymized with S. fuscus but retained as a valid subspecies by some authors. Counts and morphometric analyses and mitochondrial DNA (COI, 16SrRNA, CytB) and nuclear DNA (rag1 and rhodopsin) comparisons of three insular species (S. rocasensis, S. sanctipauli and S. trindadensis) and three other South Atlantic species (S. fuscus, S. variabilis and S. pictus) were carried out in the present study. Analyses of the principal components obtained by traditional multivariate morphometry indicate that the species in general have similar body morphology. Molecular analyses revealed conspicuous similarity between S. rocasensis and S. sanctipauli and between S. trindadensis and S. fuscus and a clear divergence between S. variabilis from Northeast Brazil and S. variabilis from the Caribbean region. Our data suggest that S. sanctipauli is a synonym of S. rocasensis, support the synonymy of S. trindadensis with S. fuscus, and reveal the presence of a likely cryptic species in the Caribbean that has been confused historically with S. variabilis.
Keywords: Damselfish; Insular species; Pomacentridae; Species delimitation; Taxonomy